Improving Foot Self-care Practices Through Health Education Intervention Programs Among Diabetic Patients: A Systematic Review - Oluchi, Sampson Emilia; Abdul Manaf, Rosliza; Ismail, Suriani; Kadir Shahar, Hayati; Udeani, Theophilus Kachidelu (Malaysian Journal of Medicine and Health Sciences, 2023)
Introduction: Diabetic foot ulcers (DFUs) remain one of the greatest significant problems of diabetes mellitus. It is a cause of main suffering and expenses for patient, and financial problem on health facilities and public. One of the strategies to overcome DFU is through health education to prevent foot ulcer, which focused in promoting foot self-care. To reach this aim, researchers had applied different educational approaches. This systematic review is to evaluate various types of educational programs in terms of its method of delivery and effectiveness. Methods: The search involved various databases; EBSCOHOST, MEDLINE, CINAHL, Cochrane library, ScienceDirect, PubMed, SAGE SringerLink, Web of Science and Wiley Online Library. It was limited to full text research articles that report intervention studies, and the writte up in English Language, the publication was from 2005 to 2021. The key words were “diabetes”, “diabetes foot”, “foot self-care”, health education and “interventions”. Results: Twenty studies were involved in this review. Nine studies were randomized controlled trials (RCTs), while eleven reported non-randomized controlled trials (NRCTs). Conclusion: There are evidences that foot care education improves foot care and diabetic foot problems. Various health education approaches, for instance foot assessment, discussion, counseling, homebased visitation and telephone calls have been shown to be effective in improving educational programs. Studies in the future should focus on RCTs in different sites and apply follow-up of long duration to provide better recommendations to healthcare practitioners on effective educational interventions to prevent DFUs.